The Mall Art Gallery. - The Mall Art Gallery, Bangkok (Bangkok : The Mall Art Gallery, 1988)
Nakbunlung, Bannarak ; Yukanthrapornpong, Tongchai ; Chandratita, Chaiyot ; Puapansakul, Pathom ; Prabpairy, Suchat ; Sriwichainan, Kamol ; Chaiyakut, Pongdej ; Steinle, Walter ; Javanalikikorn, Kade ; Pungkasamesomboon, Thaiwijit ; Tiparat, Pisan ; Suffern Osborne, Joseph Richard ; Atimana, Utis ; Boonma, Montien ; Hongpaeng, Thongsak ; Gunta-In, Amnuay ; De Vleeschauwer, Jan ; etc.
The Mall Art Gallery, Bangkok, 1988
boek